Values in foreign policy investigating ideals and interests - Srinivasan, Krishnan, 1937-; Mayall, James; Pulipaka, Sanjay (Rowman & Littlefield International Ltd, 2019)
"This books throws light on whether Asian values constitute a specific genre that differentiates Asia from the West and feeds into its nations' foreign policies, and whether there is a basic difference of opinion on values or merely an aspect of contemporary power politics"--